2020
DOI: 10.3390/nano10061089
|View full text |Cite
|
Sign up to set email alerts
|

Densification-Induced Structure Changes in Basolite MOFs: Effect on Low-Pressure CH4 Adsorption

Abstract: Metal-organic frameworks’ (MOFs) adsorption potential is significantly reduced by turning the original powder into pellets or granules, a mandatory step for their use at industrial scale. Pelletization is commonly performed by mechanical compression, which often induces the amorphization or pressure-induced phase transformations. The objective of this work is the rigorous study of the impact of mechanical pressure (55.9, 111.8 and 186.3 MPa) onto three commercial materials (Basolite C300, F300 and A100). Phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
(86 reference statements)
1
11
0
Order By: Relevance
“…This is in contrast to the 3D cubic HKUST-1 crystals, which despite their smaller average particle dimension (around 10–20 μm (ref. 99)), possess surface-area-to-volume-ratios that are two orders of magnitude lower such that the GO sheets are unable to support their mass.…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast to the 3D cubic HKUST-1 crystals, which despite their smaller average particle dimension (around 10–20 μm (ref. 99)), possess surface-area-to-volume-ratios that are two orders of magnitude lower such that the GO sheets are unable to support their mass.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that methods that rely on adsorption with solid sorbents are promising in the enrichment of lean methane-air mixtures [21,32,[36][37][38]. The various adsorption beds were tested: activated carbon (AC) [39,40], MOF [38], honeycomb monolithic carbon fiber composites [37], zeolitic imidazolate frameworks (ZIFs) [41], carbon composites derived from macadamia nut shell (MNSs), carbon nanotubes (CNTs) [21], carbon molecular sieve (CMS) [42,43], Ba exchanged titanium silicate (Ba-ETS-4) [44], etc.…”
Section: Enrichment Methodsmentioning
confidence: 99%
“…54,78,79 However, mechanical compression route is commonly used for MOFs densification due to its comparative advantage over the other techniques. 71,80 Mechanical compression has been widely used in the densification of MOFs because the procedure is inexpensive and does not require the use of organic solvent or water-based binders. 71 However, an increase in applied pressure does not translate into an improve structural properties of densified MOFs.…”
Section: Effect Of Densification Techniques On Density and Textural Propertiesmentioning
confidence: 99%